Assessment of Antioxidant Potential of Pomegranate Fruit By-Products via a Direct Approach Using a Simple QUENCHER Method. (27th November 2019) - Shahbaz, Hafiz Muhammad; Park, Eun-Joo; Kim, Gui-Ran; Akram, Kashif; Kwon, Joong-Ho
Abstract: Fruit and vegetable processing industries produce substantial quantities of phenolic-rich by-products that could be potential sources of natural antioxidants. The measurement of antioxidant activity in plant materials is mostly limited to extraction-based procedures that have several limitations. In this study, a relatively new direct approach, the QUENCHER (quick, easy, new, cheap, and reproducible) procedure was applied to measure total antioxidant capacity in pomegranate fruit by-products, including peel, pith, carpellary membranes, and seeds. Freeze-dried ground samples were directly mixed with free radical solvents in a single operation rather than separating the extract from solid samples. Efficacy of the direct procedure was evaluated against a routine extraction-based procedure using 2, 2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS); 2, 2-diphenyl-1-picrylhydrazyl (DPPH); and ferric reducing antioxidant power assays. Pomegranate peel showed the highest total antioxidant capacity, followed by pith, carpellary membranes, and seeds. Total antioxidant capacity values determined by the direct procedure were significantly higher ( P < 0.05) than those measured by the extraction procedure. The obvious advantages of the QUENCHER procedure over extraction-based procedures are that it would reduce the complexity of separating bound phenolics and antioxidant compounds, as well as the time and conditions required for unit extraction operations. The conversion of industrial waste into valuable ingredients would be advantageous for development of pomegranate supplements and added-value products.